Advanced computational intelligence paradigms in healthcare - 3 - Sordo, Margarita (Studies in Computational Intelligence,, 2008)
Advanced Computational Intelligence (CI) paradigms are increasingly used for implementing robust computer applications to foster safety, quality and efficacy in all aspects of healthcare. This research book covers an ample spectrum of the most advanced applications of CI in healthcare. The first chapter introduces the reader to the field of computational intelligence and its applications in healthcare. In the following chapters, readers will gain an understanding of effective CI methodologies in several important topics including clinical decision support, decision making in medicine effectiveness, cognitive categorizing in medical information system as well as intelligent pervasive healthcare systems, and agent middleware for ubiquitous computing. Two chapters are devoted to imaging applications: detection and classification of microcalcifications in mammograms using evolutionary neural networks, and Bayesian methods for segmentation of medical images. The final chapters cover key aspects of healthcare, including computational intelligence in music processing for blind people and ethical healthcare agents. This book will be of interest to postgraduate students, professors and practitioners in the areas of intelligent systems and healthcare.